Sistem Pengelolaan Kelompok Tani Tembakau Desa Cimeuhmal Untuk Meningkatkan Efisiensi dan Kesejahteraan Petani - Danuartha Danuartha; Cantika Mauly Nur Zahra; Hafizh Alfaris (STKIP Taman Siswa Bima, 2024)
In Pasir Malang Hamlet, Cimeuhmal Village, Tanjungsiang Subang District, there are five tobacco farmer groups, including Kiara Farmer Group 3, Kiara Farmer Group 2, Lembah Barokah Farmer Group, Mekar Mandiri Farmer Group and Sugih Mukti Farmer Group. Farmers are the main actors in producing agricultural products. To increase the productivity of agricultural quality, it is necessary to support various technologies in agriculture. In this study, a farmer group management system was developed with the title